The role of selective venous sampling in patients with non-localized primary hyperparathyroidism - Gök, İlhan (Turk J Surg, 2020)
OBJECTIVES: The aim of this observational clinical study was to evaluate the success of angiographic selective venous sampling (ASVS) in locating parathyroid adenoma in patients with primary hyperparathyroidism (PHPT), in whom the other imaging modalities have failed, and and to evaluate its possible contribution to the applicability of minimal invasive surgery. MATERIAL AND METHODS: Fifty-five patients who were admitted to our hospital’s General Surgery department between January 2012 and January 2015 for PHPT in whom ultrasound and sestamibi scintigraphy have failed to localize the diseased gland were included to the study. Patients were divided into two groups: those who underwent ASVS and those who did not. The outcomes of patients were reviewed retrospectively. RESULTS: Among 55 patients, 20 underwent ASVS. ASVS successfully lateralized the diseased gland in 17 (85%) patients, and minimally invasive parathyroidectomy could be performed in 14 (70%) patients. The cut-off value of parathormon gradient was considered 10% for lateralization and the accuracy of ASVS in lateralization was 94.1%. In 11 (59%) patients, the superior-inferior discrimination could be achieved in addition to lateralization. CONCLUSION: ASVS has a high sensitivity in locating the diseased gland in patients with PHPT in whom ultrasound and sestamibi scan have failed, and thereby, rendering the performance of minimally invasive surgery possible. Further studies may reveal the role of ASVS in providing useful information about not only lateralization but also the superior-inferior discrimination.